2016
DOI: 10.1371/journal.pgen.1005818
|View full text |Cite
|
Sign up to set email alerts
|

Innovation of a Regulatory Mechanism Modulating Semi-determinate Stem Growth through Artificial Selection in Soybean

Abstract: It has been demonstrated that Terminal Flowering 1 (TFL1) in Arabidopsis and its functional orthologs in other plants specify indeterminate stem growth through their specific expression that represses floral identity genes in shoot apical meristems (SAMs), and that the loss-of-function mutations at these functional counterparts result in the transition of SAMs from the vegetative to reproductive state that is essential for initiation of terminal flowering and thus formation of determinate stems. However, littl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
45
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 57 publications
(49 citation statements)
references
References 59 publications
4
45
0
Order By: Relevance
“…These results revealed that most of the HbMADS-box genes (69.2% belong to the first, second, and third groups) within the same group shared conserved exon-intron structures, and the other HbMADS-box genes (30.8% of the fourth to eighth groups) with the different exon-intron structures may belong to distinct types of HbMADS-box genes in the rubber tree (Table S5). These characteristics are consistent with the features of MADS-box genes in other flowering plants, such as Arabidopsis, Oryza sativa, and Vitis vinifera [45][46][47].…”
Section: Gene Structures and Sequence Characteristics Of Hbmad-box Genessupporting
confidence: 85%
“…These results revealed that most of the HbMADS-box genes (69.2% belong to the first, second, and third groups) within the same group shared conserved exon-intron structures, and the other HbMADS-box genes (30.8% of the fourth to eighth groups) with the different exon-intron structures may belong to distinct types of HbMADS-box genes in the rubber tree (Table S5). These characteristics are consistent with the features of MADS-box genes in other flowering plants, such as Arabidopsis, Oryza sativa, and Vitis vinifera [45][46][47].…”
Section: Gene Structures and Sequence Characteristics Of Hbmad-box Genessupporting
confidence: 85%
“…Epistasis, or the interaction between genes, plays an important role in controlling complex inheritance [ 34 ]. For instance, Dt1 exerts an epistatic effect on Dt2 in the regulation of plant height in soybean [ 35 , 36 ]. In this study, we detected three SAL for plant height using all tested accessions (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In the literature, the soybean stem growth habit genes ( Dt1 and Dt2 ) and E genes conferring flowering and maturity were considered to be related to MSN (Chang, et al., 2018; Fang, et al., 2017), but the Dt1 gene was not identified in our study. That might be because the breeding priority in NEC tended to be semi‐determinant stem termination conferred by a dominant allele Dt2 in the genetic background of Dt1 (Bernard, 1972; Liu et al., 2016; Xue, Wei, Tang, & Liu, 2015). The present candidate MSN gene results as a gene system are to be further validated, which may take great future effort.…”
Section: Discussionmentioning
confidence: 99%